Implementasi Artificial Intelligence dalam Meningkatkan Keunggulan Bersaing pada Usaha Mikro, Kecil dan Menengah - Kalifatullah Ermaya (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are business entities that play a strategic role in the Indonesian economy. Continuously evolving information technology can increase efficiency, productivity, and creativity in business. One information technology that MSMEs can utilize is artificial intelligence (AI). This research was conducted to examine the use of artificial intelligence by MSMEs as an effort to increase competitive advantage in their business development. This research utilized a literature review method as an approach to collect, analyze, and formulate information from various scientific publications, including books, online articles, journals, theses, and other written sources. The study concluded that implementing artificial intelligence in business decision-making in MSMEs offers many substantial benefits, although it also faces specific challenges. AI significantly improves operational efficiency and competitive advantage by processing data quickly and accurately, allowing management to concentrate on strategic initiatives. However, the implementation of artificial intelligence should be carried out gradually through trials and evaluation of results, so that the technology adaptation process is more efficient and minimizes the potential for resource waste. Keywords: MSMEs, Artificial Intelligence, Competitive Advantage